Environmental and genealogical effects on emergence of cranial morphometric variability in reintroduced American martens - Howell, Paige E.; Lundrigan, Barbara; Scribner, Kim T. (Journal of Mammalogy, 2016)
Exposure of individuals to novel environmental conditions generally favors locally adapted phenotypes and can influence the likelihood of successful dispersal or the success of translocation efforts. We used geometric morphometrics to characterize American marten ( Martes americana ) skull morphology for descendants of animals reintroduced to the Upper Peninsula of Michigan, USA (~44,000 km2) from genetically distinct source populations. Using univariate and multivariate analyses, we quantified associations between interindividual variation in skull shape and size, genealogical relationships, past introduction history, local harvest density of competitors, and contemporary landscape features we hypothesized would be related to diet. Effects of other sources of variation including shared ancestry (source population, geographic distance, and coancestry among descendants), sex, and age were also evaluated. Descendant skull shape was related to progenitor source population, sex, and age. In contrast to strong associations between spatial genetic structure based on neutral molecular markers and measures of landscape effects on dispersal, variation in skull shape among descendants was not associated with geographic distance or landscape features. Our study addressed a critical issue regarding a widely used conservation prescription. Specifically, when individuals are transplanted to reestablish extirpated species, do their descendants retain the features of the source population(s), or do they adapt to local conditions? Marten skull shape following reintroduction events is most likely determined by a combination of differences in morphology of source populations and geographic variation in habitat, rather than being influenced by a single factor.